THE FACTITIOUS DISORDER: THE ANALYSIS OF MUNCHAUSEN SYNDROME BY PROXY CASES FROM TURKEY - Polat, Oğuz; Akpınar, Ayşe; Önal, Osman (International Journal of Psychosocial Rehabilitation, 2024)
Child abuse is a vital subject matter with a broad definition ranging from neglecting a child's basic physiological and emotional needs to causing his/her death by the negligent and abusive caregiver(s). In the article, as a form of child abuse, Munchausen Syndrome by Proxy is defined, discussed, and presented with two MSBP cases selected from Turkey. The initial aim of the article is to present the cases from Turkey to analyze and investigate the reasons and consequences of MSBP as the fabricated disease and as a form of child abuse on the victims in the framework of etiology, prevalence, and prevention methods on the cases in Turkey. In addition to that, the secondary aim of the article is to elevate public awareness of the phenomenon with respect to the protection of children's rights. The perpetrators are the mother(s) of the victim children in the majority of the MSBP cases. Based on the analysis of the aforementioned cases from Turkey, the potential fatal consequences of the MSBP and the crucial role of medical staff in determining the cases and reporting them to the authorities abruptly so as to protect the children from the abuse and probable harms of the syndrome are discussed